Second-best analysis of European energy policy: Is one bird in the hand worth two in the bush? - Michael Hübler; Oliver Schenker; Carolyn Fischer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2015)
This paper studies policy instruments that correct insufficient learning-by-doing (LbD) and research and development (R&D) of renewable electricity technologies and insufficient investments in energy efficiency (EE) in the presence of carbon pricing. The theoretical model analysis shows how to re-adjust the first-best in second-best situations, in which one of the policy instruments is restricted. Calibrated to the European power sector, the first-best choice of all instruments reduces the climate policy cost by one third. Feed-in tariffs turn out to be good substitutes for LbD, but not for R&D or EE subsidies.
urn:nbn:de:bsz:180-madoc-401625
Keywords: C61; O33; Q48; Q54; Q55; 330; second-best; climate policy; energy policy; feed-in tariff; power sector; EU